Implementasi Pendidikan Karakter Peduli Lingkungan pada Mata Pelajaran Ilmu Pengetahuan Alam (IPA) - Nurfika, Asri Dwi (Didaktika, 2022)
Character education is an effort to educate children to make good choices and implement them in their daily activities so that they are able to play a real role in their surroundings. Character building from an early age provides a strong foundation for shaping the character of caring for the environment. Attitudes and behaviours that always try to avoid damage to the surrounding environment and restore natural damage that has occurred are the character of caring for the environment. A healthy school environment is needed to support the teaching and learning process and to adjust to clean and healthy living habits. This study aims to find out the picture of character education caring for the environment in science subjects at SDN Kalibata 04 Pagi. The narrative inquiry method was used for this study with data collection techniques in the form of storytelling, field notes, interviews, and documentation. Based on research that has been carried out it has been applied for a long time to habituate environmental care. However, due to the COVID-19 pandemic, instilling the character of caring for the environment, it can only be done in remotely active learning. So student’s interest in caring for the environment cannot be seen in distance learning. Therefore, researchers developed an environmentally caring character education program in science subjects during face-to-face learning to meet four aspects, including cognitive, affective, psychomotor, and interests.